A case series of disseminated porokeratosis - J Logeshwari; Nippa Devi A Patel; Sirisha Varala; Ananthula Venkata Krishna (Wolters Kluwer Medknow Publications, 2021)
Porokeratosis is an autosomal dominant disorder of epidermal keratinization resulting from abnormal expansion of latent clones following chronic ultraviolet exposure or immunosuppression. Various clinical and morphological variants of porokeratosis are present, among which disseminated superficial actinic porokeratosis (DSAP) is the most common subtype located predominantly on the sun exposed areas, whereas disseminated superficial porokeratosis (DSP) is present both on the sun exposed and sun protected areas including oral mucosa and genitalia. Porokeratosis is characterized clinically by annular plaques with atrophic center and thready border and histologically by the presence of cornoid lamella. DSAP may be missed because of its inconspicuous nature in dark skinned individuals and may sometimes be mistaken for actinic keratoses in sun-damaged skin. Here, we report a case series of five patients with disseminated porokeratosis with varied presentations.